Avaliação dos sedimentos em suspensão com o uso de imagens multiespectrais nos reservatórios de Caçu e Barra dos Coqueiros GO - Pinese Júnior, José Fernando (2014)
Large amounts of sediment transported by rivers, coming from the erosive action of water on the basin soil, causing degradation of water bodies and significant damages to the population, to socioeconomic development and to the natural environment. The processes of sediment production and deposition along a watershed are natural phenomena, but its effects can be magnified by the man influence through the disordered deforestation, construction, mining and improper management of agricultural activities. During the sediments transport and deposition in water bodies there is a color change in the water due to the concentration of dissolved or suspended materials. The water bodies color is directly linked to their inherent optical properties of absorption and spreading. These properties change according to the concentration, nature and types of dissolved and particulate materials in the water. The Normalized Difference Water Index (NDWI) is a method developed by McFeeters (1996) with the purpose of delineates features in the water, such as Active Optical Components, highlighting their presence, and found by digital images processing. The author modified the NDVI formula reversing the variables and using the green band instead of the red band in order to obtain better results attentive on water analysis. In this sense, the work is presented in order to promote by analyzes, descriptions, maps and systematic studies, the assessment of water quality NDWI method in the reservoirs of Caçu and Barra dos Coqueiros Hydropower Plants (HPPs), in Claro river, located in the southwestern portion of Goiás state - Brazil, evaluating the determination of suspended sediments method in lentic environments by multispectral images. Analyses of NDWI indices produced visually coherent data, but could not find an index for correlations between real data or even a calibration value to help in the determination of suspended sediment concentration. The NDWI method enables visual inspection of sediment yield characteristics for a given location, but must be in the same scene from the same date to become comparable. It is possible to make notes of places with higher sediment production and flow spread. Is found in the statistical analysis a low correlation between the suspended sediments concentration obtained from field sampling and from values of NDWI processing. The visual analysis of maps with the NDWI results is valid to indicate regions of interest for field sampling, analyzing patterns of sediment behavior also in rainfall seasonality periods.